Letter to the Editor: The Case for Publicly Funded Headache Surgery in Germany - Leonard Knoedler (Elsevier, 2021)
Summary: Headache surgery has become a considerable therapeutic option in headache treatment and is of rising interest in the German medical sector. This viewpoint outlines the need for reimbursement of headache surgery in the German healthcare system and demonstrates its cost-effectiveness. Using state-of-the-art patient selection algorithms, the authors found headache surgery to be cost-effective within 7.2 to 6.3 years. Of note, the approach presented is not limited to the German healthcare system.